2017
DOI: 10.1002/mds.27069
|View full text |Cite
|
Sign up to set email alerts
|

No clear support for a role for vitamin D in Parkinson's disease: A Mendelian randomization study

Abstract: Background Observational studies have found that relative to healthy controls, patients with Parkinson’s disease have lower circulating concentrations of 25-hydroxyvitamin D, a clinical biomarker of vitamin D status. However, the causality of this association is uncertain. We undertook a Mendelian randomization study to investigate whether genetically decreased 25-hydroxyvitamin D concentrations are associated with PD to minimize confounding and prevent bias because of reverse causation. Methods As instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Examples of such markers include pesticide‐induced gene mutations and biological markers of oxidative stress . Techniques such as Mendelian randomization, whereby a genetic marker associated with the levels of a factor associated with risk such as vitamin D or serum urate can avoid error or bias associated with exposure measurements. This method can be used to corroborate findings and improve causal inference when positive.…”
Section: The Next 10 Yearsmentioning
confidence: 99%
“…Examples of such markers include pesticide‐induced gene mutations and biological markers of oxidative stress . Techniques such as Mendelian randomization, whereby a genetic marker associated with the levels of a factor associated with risk such as vitamin D or serum urate can avoid error or bias associated with exposure measurements. This method can be used to corroborate findings and improve causal inference when positive.…”
Section: The Next 10 Yearsmentioning
confidence: 99%
“…We have also seen a surge of MR studies in the field of PD specifically exploring the causal role of several circulating biomarkers. [10][11][12][13][14][15] For example, a recent MR study reported a significant causal association with a lifelong PD risk reduction of 3% per 10-μg/dL increase in serum iron levels. 12 Most recently, another study further reported a risk reduction of 18% with a lifetime exposure of 5-kg/m 2 higher body mass index.…”
Section: Related Article Editorialmentioning
confidence: 99%
“…Moreover, our report showed that the risk effects of the rs6013897 variant were statistically significant in most subgroups, and there was no significant heterogeneity within each subgroup variable, which suggested that these variables did not modify this association. Some previous research has also reported that rs6013897 can affect the risk of Parkinson disease (PD), aggressive prostate cancer, and bone mineral density at the femoral neck (FN-BMD) by affecting the 25(OH)D 3 concentration (Dimitrakopoulou et al, 2017;Larsson et al, 2017;Larsson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%